2008
DOI: 10.1590/s0004-282x2008000500008
|View full text |Cite
|
Sign up to set email alerts
|

Control of psychomotor agitation and aggressive behavior in patients with autistic disorder: a retrospective chart review

Abstract: -Objective:To evaluate the efficacy of pharmacotherapy on the symptoms of psychomotor agitation and aggressive behavior in a sample of patients with autistic spectrum disorder. Method: The charts of all patients with a diagnosis of autistic spectrum disorder, receiving care for psychomotor agitation and/or aggressive behavior in two psychiatric outpatient departments between 2001 and 2006, were reviewed. The Clinical Global Impression-Severity and -Improvement scales (CGI-S and CGI-I) were applied to the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
9
0
4
Order By: Relevance
“…According to the Diagnostic and Statistical Manual of Mental Disor ders, 4 th Edition (DSMIV), the PDD group has five diffe rent cate gories: autistic disorder, Rett's disorder, childhood di sintegrative disorder, Asperger syndrome and pervasive de ve lopmental disorder -not otherwise specified (PDDNOS) 1 . Associated symptoms such as hyperactivity 2 , aggressi veness, epilepsy and insomnia are common and aggravate the clinical condition, which in some cases may require pharmacological management 3 . Bearing in mind that the neurobiological origin of PDDs remains to be fully clarified, there are no specific diagnostic markers of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disor ders, 4 th Edition (DSMIV), the PDD group has five diffe rent cate gories: autistic disorder, Rett's disorder, childhood di sintegrative disorder, Asperger syndrome and pervasive de ve lopmental disorder -not otherwise specified (PDDNOS) 1 . Associated symptoms such as hyperactivity 2 , aggressi veness, epilepsy and insomnia are common and aggravate the clinical condition, which in some cases may require pharmacological management 3 . Bearing in mind that the neurobiological origin of PDDs remains to be fully clarified, there are no specific diagnostic markers of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Autism is a complex developmental disorder with multiple etiologies and different severity degrees 25 . These disorder is commonly associated with other morbidities [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…We can also think that the association of autism and ADHD can be comorbidity or still a distinct phenotype of autism. Elucidating this problem can predict the prognosis for these children and can be very important for therapeutic planning for autistic children 24 , especially because those children have been treated with different classes of medications 25 . This study aims to estimate the frequency of symptoms of ADHD in patients with autistic disorder.…”
mentioning
confidence: 99%
“…They also reviewed the possible problems of weight gain and tardive dyskinesia. ''Second-generation antipsychotic medications" were studied by others [303] who reported that these medications seem to reduce psychomotor agitation and aggressive behavior. Fido and Al-Saad [304] reported on olanzapine in particular, concluding that this treatment can alleviate irritability, hyperactivity, and lethargy.…”
Section: Atypical Antipsychotic Medicationsmentioning
confidence: 99%